KONTRIBUSI MOTIVASI DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR SISTEM OPERASI KELAS XI TKJ DI SMK NEGERI 1 BENDAHARA - Oslan Khalid; Yasdinul Huda; Titi Sriwahyuni (Universitas Negeri Padang, 2016)
The purpose of this study is to reveal the contribution of motivation and learning environment to the learning outcomes of subject’s operating systems class XI student of Computer Engineering Network at SMK Negeri 1 Bendahara. This type of research is associative Correlation. The population in this study all students of class XI Computer Network SMK Negeri 1 Bendahara, consists of two classes totaling 64 people. The sampling technique was randomly (simple random sampling). Data obtained from the student learning outcomes subject teachers’ operating system SMK Negeri 1 Bendahara. While the motivation and learning environment of data collected through questionnaires using Linker scale that has been tested for validity and reliability. Data were analyzed using multiple regression method with the help of software Microsoft Excel 2007 and SPSS v.16. The results of analysis showed: (1) Motivation and learning environment together contributed 17.95% to the learning outcomes of class XI student of SMK Negeri 1 Bendahara; (2) Motivation contributed 11.64% to the learning outcomes of class XI student of SMK Negeri 1 Bendahara; (3) Environmental Learning contributed 11.08% to the learning outcomes of class XI student of SMK Negeri 1 Bendahara. So we can conclude that the motivation and learning environment contribute to the learning outcomes, the higher motivation and better learning environment, the learning outcomes will be better. Keywords: Motivation, Environmental Learning, Associative correlation, simple random sampling, multiple regressions.